Associations of CYP1 polymorphisms with risk of prostate cancer: an updated meta-analysis. Issue 3 (1st March 2019) - Zhu, Wei; Liu, Hailang; Wang, Xinguang; Lu, Jinjin; Zhang, Huiping; Wang, Shaogang; Yang, Weimin
Abstract : Background. The results of previous studies on the association between polymorphisms of CYP1A1 and CYP1B1 and prostate cancer (PCa) susceptibility are inconsistent. The aim of the present study was to conduct a meta-analysis in order to better estimate this association.Methods. A systematic search was carried out on PubMed, Embase, Cochrane Library, and China National Knowledge Infrastructure (CNKI) databases for relevant articles published up to 15 August 2018. Pooled odds ratios (ORs) and 95% confidence intervals were obtained using fixed-effect or random-effect models.Results. A significant association was found between the CYP1A1 rs1048943 polymorphism and PCa in the overall population (B [the minor allele] vs. A [the major allele]: OR = 1.20, 95% confidence interval (CI) = 1.04–1.39, P =0.014; AB vs. AA: OR = 1.24, 95% CI = 1.02–1.51, P =0.029; BB + AB vs. AA: OR = 1.25, 95% CI = 1.04–1.50, P =0.018) and Asian population (B vs. A: OR = 1.32, 95% CI = 1.11–1.56, P =0.001; BB vs. AA: OR = 1.81, 95% CI = 1.20–2.72, P =0.005; AB vs. AA: OR = 1.30, 95% CI = 1.03–1.64, P =0.029; BB + AB vs. AA: OR = 1.38, 95% CI = 1.11–1.73, P =0.004; BB vs. AA + AB: OR = 1.58, 95% CI = 1.08–2.01, P =0.019), but not in the Caucasian population. Moreover, we found that the rs4646903 polymorphism was associated with a significant increase in the risk of PCa in the Asian population (AB vs. AA: OR = 1.43, 95% CI = 1.13–1.80, P =0.003) and Caucasian population (BB vs. AA: OR = 2.12, 95% CI = 1.29–3.49, P =0.003).Conclusion. This meta-analysis revealed a clear association between rs1048943 and rs4646903 polymorphisms of the CYP1A1 gene but not between CYP1B1 rs10012, rs162549, rs1800440, and rs2551188 polymorphisms and the risk of PCa.